Les peintures mates d’Antoine Wiertz (1806-1865) - Karine Janssen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Faced with the works of Antoine Wiertz, a question arises: Is the washed-out and mat appearance of some of his paintings an artistic intent, or a consequence of alteration. Painted with a technique developed by the artist to achieve a matt appearance, these works are in fact subject to a slow degradation process. Based on the artist’s writings, his particular painting process was reproduced and analysed scientifically. This study concludes that the appearance of those artworks is not a result of the artist’s intent but caused by the combined action of various changes inherent to the painter’s technique.